Biophysical characterisation of the mechanisms regulating sarcoplasmic reticulum K+ channel gating - O'Brien, F (2015)
Intracellular Ca2+-release from the sarcoplasmic reticulum (SR) occurs through highly specialised Ca2+-release channels called ryanodine receptors (RyR) in a process known as excitation-contraction coupling (EC-coupling) in striated muscle. The RyR is the main ion-channel mediating Ca2+-release from the SR but the SR also contains many other ion-channels and proteins, with many of unknown physiological role. For example, two SR K+ channels, TRIC-A and TRIC-B, have recently been identified and are thought to play a key role in supporting intracellular Ca2+ movements across the SR. The TRIC double knockout (DKO) mouse dies in embryonic heart failure and the TRIC-B knockout (KO) dies in respiratory failure immediately after birth, highlighting their important roles in different tissue types. The TRIC-A KO mouse survives until adulthood, however, there are SR structural abnormalities and compromised Ca2+ release. I have focused on characterising and comparing the single-channel properties of the native SR K+ channels from WT and TRIC-A KO mouse skeletal muscle. I have investigated if the SR K+ channels can gate in a cooperative manner when multiple SR K+ channels are present in the bilayer. Since TRIC and RyR channels are both located in high abundance in the junctional SR regions, I have examined whether the SR K+ and RyR channels also gate in a cooperative manner when both are present in a bilayer. In addition to voltage-regulation of native SR K+ channels, I have characterised the pH sensitivity of the SR K+ channels from WT and TRIC-A KO tissue. Finally, I investigated if the mouse isoform of TRIC-A could be purified using the Wheat germ cell-free system and incorporated into bilayers without loss of function. In summary, this thesis describes novel mechanisms of regulation of ion-channels that are involved in the process of Ca2+-release from the SR. By focusing on the biophysical properties of SR K+ channels, I have highlighted the complexity of the ionic fluxes that are thought to be required to maintain normal EC-coupling in striated muscle.